Forecasting the Future at Siemens: Innovations in Time Series Analysis with Machine Learning Models - Simões, Guilherme Costa Marques Lopes (2024)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science